Improving Student Literacy in Indonesian Language Learning Storytelling Method for Class V SDN Nyormanis 02 - Aisyiyah Rodiyah; Amelia Khoiruna; Rila Hardiansyah (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2025)
The aim of this research is to find out what factors cause students to be less interested in learning literacy and to find out whether there is an increase in student literacy when learning Indonesian using the storytelling method. This research was carried out in class 5 at SDN Nyormanis 2 using the classroom action research method. This method is implemented through cycle I and cycle II. Cycle I was carried out by giving a test without any action, in cycle II before being given the test the researcher carried out an action where the researcher told a short story, explained the material using the storytelling method, then the researcher gave the test. In the first cycle, it was discovered that there were still students who got lower grades. In cycle II, it is known that students get increased grades. Based on field conditions, the internal factor causing the low literacy interest of students at SDN Nyormanis 02 class V is the students' low reading ability. Lack of parental awareness of the importance of education for children. It can be concluded that the storytelling method is effective in improving students' literacy skills in Indonesian language subjects.